The Influence of Discipline and Work Facilities on Employee Performance with Motivation as an Intervening Variable at the Danau Teluk District Office, Jambi City - Firnando, Elly; Yamali, Fakhrul Rozi; Hapsara, Osrita (Dinasti International Journal of Management Science, 2026)
The purpose of this study is to describe discipline, work facilities, motivation and employee performance in Danau Teluk District, Jambi City and to analyze the influence of discipline and work facilities partially and simultaneously directly and indirectly on employee motivation and performance, as well as to analyze motivation on employee performance. To answer the research objectives, this study is supported by theoretical studies related to the research variables, namely discipline, work facilities, motivation and employee performance. In addition, the author also looked for relevant previous research in the form of articles/journals and previous theses to support this research. The population in this study were 60 employees of Danau Teluk District, Jambi City with conditions in 2025 and sampling using total sampling where the entire population was used as a sample of this study. The data analysis technique used in this study was through path analysis followed by hypothesis testing through the F test (Simultaneous) and t test (Partial). From the path analysis test conducted, it was found that discipline and work facilities influenced motivation by 75% while the rest was influenced by other variants. Discipline and work facilities have a 68.5% influence on employee performance, and in the final structure, motivation has a 65.2% influence on employee performance, with the remainder influenced by variables outside of this study. This study concludes that discipline, work facilities, motivation, and employee performance are in a fairly satisfactory and high condition. In addition, discipline and work facilities partially and simultaneously have a positive and significant influence on employee motivation and performance in the Danau Teluk District, Jambi City. Likewise, motivation has a positive and significant influence on employee performance.